Shear Wave Dispersion in Lean Versus Steatotic Rat Livers. (1st June 2015) - Barry, Christopher T.; Hazard, Christopher; Hah, Zaegyoo; Cheng, Gang; Partin, Alexander; Mooney, Robert A.; Chuang, Kuang-Hsiang; Cao, Wenqing; Rubens, Deborah J.; Parker, Kevin J.
Abstract : Objectives: The precise measurement of fat accumulation in the liver, or steatosis, is an important clinical goal. Our previous studies in phantoms and mouse livers support the hypothesis that, starting with a normal liver, increasing accumulations of microsteatosis and macrosteatosis will increase the lossy viscoelastic properties of shear waves in a medium. This increase results in an increased dispersion (or slope) of the shear wave speed in the steatotic livers. Methods: In this study, we moved to a larger animal model, lean versus obese rat livers ex vivo, and a higher‐frequency imaging system to estimate the shear wave speed from crawling waves. Results: The results showed elevated dispersion in the obese rats and a separation of the lean versus obese liver parameters in a 2‐dimensional parameter space of the dispersion (slope) and shear wave speed at a reference frequency of 150 Hz. Conclusions: We have confirmed in 3 separate studies the validity of our dispersion hypothesis in animal models.